About granulation of bird droppings - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (ТДАТУ, 2021)
Poultry farms produce much more waste than meat and eggs. Poultry farms spend money on the disposal of valuable organic raw materials. Poultry droppings contain aggressive chemicals that make it impossible to dispose of, as this leads to soil and water poisoning. One of the main ways to dispose of droppings is to convert them into pellets. This form can be used to fertilize soils and even for heating.
Keywords: рoultry; disposal; droppings; pelleting; microelements; pelletizing product; compost; microorganisms